Baroque horrors : roots of the fantastic in the age of curiosities - Castillo, David R., 1967- (University of Michigan Press, 2010)
"Baroque Horrors turns the current cultural and political conversation from the familiar narrative patterns and self-justifying allegories of abjection to a dialogue on the history of our modern fears and their monstrous offspring. When life and death are severed from nature and history, "reality" and "authenticity" may be experienced as spectator sports and staged attractions, as in the "real lives" captured by reality TV and the "authentic cadavers" displayed around the world in the Body Worlds exhibitions. Rather than thinking of virtual reality and staged authenticity as recent developments of the postmodern age, Castillo looks back to the Spanish baroque period in search of the roots of the commodification of nature and the horror vacui that accompanies it." "Aimed at specialists, students, and readers of early modern literature and culture in the Spanish and Anglophone traditions as well as anyone interested in horror fantasy, Baroque Horrors offers new ways to rethink broad.